Paulo Moura e a bossa nova Instrumental - Cléber José Bernardes Alves (2019)
This thesis presents an investigation of the performance and arrangement practices of the brazilian musician Paulo Moura, based on the transcription and analysis of seven phonograms from the albums Paulo Moura Hepteto – Mensagem (1968) and Paulo Moura Quarteto (1969). Its objective is the possibility of an idiomatic construction of the saxophone, with brazilian characteristics, in the interpretation, improvisation, as well as the arrangement. It approaches, initially, the need for a systematization of the material for an instrumental practice and the investigation of theoretical references about brazilian music. It then presents the historical context of Paulo Moura comprising the analyzed period of his life (GRYNBERG, 2011; SPIELMANN, 2008; FRANÇA, 2015). Finally, at the heart of the research, we have the analysis (DOBBINS, 1986; GRELA, 1992; GUEST, 1996; ALMADA, 2000; BERLINER, 2001; LOWELL E PULLIG, 2003; TOMARO; WILSON, 2009) of transcriptions of the songs Wave, O Homem do Meu Mundo, Outubro, Lamento no Morro, Aos Pés da Cruz, Meu Lugar and Razão, elucidating the aspects of performance that characterize Paulo Moura's interpretive and improvisational style, as well as his way of arranging.